Predictor Factors Affecting Seroconversion Post-InfluenzaVaccination in the Elderly - Nursyirwan, Saskia Aziza; Koesnoe, Sukamto; Wahyudi, Edy Rizal (Jurnal Penyakit Dalam Indonesia, 2017)
Introduction. The influenza vaccine as the most effective method for preventing influenza virus infection currently has lower efficacy in the elderly than younger adults due to change of immune response as well as other risk factors. This study aims to identify predictor factors affecting seroconversion post-influenza vaccination in elderly. Methods. retrospective cohort study in the elderly population in East Jakarta Posyandu who got the influenza vaccine. A total of 277 subjects with antibody titre pre and one month post-vaccination influenza were examined. Risk factors such as age, gender, exercise status, smoking status, type 2 diabetes, pulmonary, and cardiovascular disease, nutritional status of MNA (Mini Nutritional Assessment), GDS (Geriatric Depression Scale), and pre-vaccination antibodi titre were assessed in each subject. Results. The proportion of elderly people who seroconverted (fourfold rise or more in antibody titer post-vaccination) was 50.9% (141/277). On multivariate analysis, the predictor factors that affect seroconversion of one month post- influenza vaccination in the elderly on the community is a no depression state (p = 0.048, OR = 2.1, CI = 1.01 to 4.30), exercise status ≥5 times per week minimal 30 minutes (p = 0.013, OR 4.0, CI 1.34 to 11.76), and not seroprotective pre-vaccination (p=0.000, OR 6.4, CI 3.40 to 11.99). Conclusion. Predictor factors affecting seroconversion post-influenza vaccination in the elderly on the community is depression status, exercise status and pre-vaccination antibody titre.